Biostimulant potential from seaweed (Kappaphycus alvarezii) on rice seedling development - La Ode Afa; Nini Mila Rahni Rahni; Andi Awaluddin Awaluddin; Wa Ode Nuraida Nuraida; La Ode M. Aslan Aslan; Noor Akbar Al-Ubaidah Al-Ubaidah; Paisal (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Seaweed (Kappaphycus alvarezii) liquid extract contains hormones, and macro and micronutrients that might benefit plant growth and development. This study aimed to evaluate the effect of a biostimulant liquid of seaweed extract on the vigor of rice seedlings. The research was conducted in the experimental field of the Faculty of Agriculture, Halu Oleo University, Kendari, Southeast Sulawesi. A factorial treatment design was conducted with a randomized block design. The first factor was the seedling method (wet sowing (S1) and dry sowing (S2)), and the second factor was six biostimulant concentrations (no biostimulant (K0), 0.8% (K1), 1.6% (K2), 2.4% (K3), 3.2% (K4), and 4.0% (K5)). The observed variables included seedling height, leaf area, number of tillers, root dry weight, and seedling dry weight. Data were analyzed using ANOVA, and DMRT at α = 0.05. The results showed that the wet sowing method produced better seedling vigor than the dry sowing method after 14 days. The wet sowing method combined with a 0.8% seaweed extract resulted in the highest seedling vigor. The present study concluded the biostimulant potential of seaweed extract for rice. Keywords: Dry sowing; Oryza sativa; seedling vigor; sowing method; wet sowing